Advances in Cardiovascular Disease Lipid Research Can Provide Novel Insights Into Mycobacterial Pathogenesis - Thirunavukkarasu, Shyamala; Khader, Shabaana A. (Frontiers in Cellular and Infection Microbiology, 2019)
Cardiovascular disease is the leading cause of death in industrialized nations and an emerging health problem in the developing world. Systemic inflammatory processes associated with alterations in lipid metabolism are a major contributing factor that mediates the development of cardiovascular diseases, especially atherosclerosis. Therefore, the pathways promoting alterations in lipid metabolism and the interplay between varying cellular types, signalling agents and effector molecules have been well studied. Mycobacterial species are the causative agents of various infectious diseases in both humans and animals. Modulation of host lipid metabolism by mycobacteria plays a prominent role in its survival strategy within the host as well as in disease pathogenesis. However, there are still several knowledge gaps in the mechanistic understanding of how mycobacteria can alter host lipid metabolism. Considering the in-depth research available in the area of cardiovascular research, this review presents an overview of the parallel areas of research in host lipid-mediated immunological changes that might be extrapolated and explored to understand the underlying basis of mycobacterial pathogenesis.